Aplastic anemia, leukemia and other cancer mortality in a cohort of shoe workers exposed to benzene. - Paci, E; Buiatti, E; Seniori Costantini, A S; Miligi, L; Pucci, N; Scarpelli, A; Petrioli, G; Simonato, Lorenzo; Winkelmann, Regina; Kaldor, J M (Scandinavian Journal of Work, Environment & Health, 1989)
Benzene is a well documented carcinogen for the hematic and lymphopoietic system, and experimental research confirms its carcinogenicity for tumors of other sites. This report presents the results of a historical cohort study in a shoe manufacturing plant in Florence where cases of aplastic anemia and leukemia were reported in the 1960s. A total of 1008 men and 1005 women were considered eligible members of the cohort. For total mortality, comparing the rates of the cohort with the national rates, the standardized mortality ratio (SMR) was 79 for the women and 95 for the men. For the men excesses of risk for aplastic anemia [SMR 1566; 95% confidence interval (95% CI) 547-3264] and leukemia (SMR 400, 95% CI 146-870) were observed. The increased risk occurred among workers first employed during the period in which benzene was used, but the expected number of cases in the subsequent period was too small to evaluate whether any reduction in risk had occurred. No increasing pattern with duration of employment was discernible.